Preliminary Study on Slotted-Electrical Discharge Diamond Face Grinding of Metal Matrix Composite - Yadav, Ravindra Nath; Yadava, Vinod (Asian Review of Mechanical Engineering, 2013)
Metal matrix composites (MMCs) are highly required in field of advanced engineering. Due to the abrasive nature of the reinforcements into matrix, machining of the MMCs is yet a challenge for manufacturing industries. In this paper, a new hybrid machining process named as slotted-electrical discharge diamond face grinding (S-EDDFG) has been proposed for machining of the end surface of the electrically conductive hard and brittle materials. The performance of the developed process has been tested on EDM machine with application of the compound grinding wheel. The role of discharge voltage, current, pulse on-time, pulse off-time and wheel RPM has been investigated on MRR and Ra during machining of the Al/SiC composite. The experimental results show that MRR increases and Ra value decreases with increase of the wheel RPM due to enhances in the flushing efficiency of the dielectric.